The Freedom to Smoke: Tobacco Consumption and Identity - Belisle, Donica (Labour / Le Travail, 2008)
The article reviews the book, "The Freedom to Smoke: Tobacco Consumption and Identity," by Jarrett Rudy.
Keywords: BOOKS – Reviews; FREEDOM to Smoke: Tobacco Consumption & Identity; The (Book); Nonfiction; RUDY; Jarrett; SMOKING